Three-dimensional solar arrays - EDGAR ROSS ALLAN (2012)
An assembly for retaining a plurality of photovoltaic modules in a three-dimensional array, the assembly including a plurality of overlapping vertically spaced grid layers each defining a plurality of horizontally spaced positions, wherein the photovoltaic modules are arranged and retained in the positions of successive grid layers in substantially non-overlapping vertical relationship so that none of the photovoltaic modules in any grid layer substantially vertically occludes any other of the photovoltaic modules in any other grid layer.